The Policy Formulation Model for the Use of the Penanggungan Cultural Heritage Area in Mojokerto Regency as a Form of Protection and Preservation of Cultural Heritage - Cik Ida Kumalasari Amirudin; Bambang Supriyono; Abdullah Said (Sekolah Pascasarjana Universitas Brawijaya, 2019)
This study aims to analyze the policy formulation model of space utilization in the cultural preservation area in Mojokerto Regency as a form of protection and preservation of cultural heritage. The author analyzes the policy formulation using a comprehensive rational model, which includes knowing the choices that people want, finding policy choices that can be implemented, assessing the consequences of each policy, assessing the comparison of the profit and loss calculations that will be obtained if the policy is implemented. The type of research used is a type of descriptive and historical research with a qualitative approach. The results showed that in the determination and decision making, the government made several considerations with a long period of time, starting from formulating the problem, advocating to the local community, choosing alternative policies using forecasting policies by taking into consideration several consequences of the policy of space utilization in the cultural heritage area if the policy is implemented. Some aspects that are taken into consideration are losses and benefits if the policy is implemented, the budget of the funds, the impact of the policy and efficiency of the policy.